Pengembangan Media Pembelajaran Komik Berbasis Kearifan Lokal Riau Materi Harmoni Ekosistem Untuk Siswa Kelas V SD IT Bunayya Pekanbaru - Mardianti, Resi; Mustika, Dea (Institut Teknologi Pendidikan Indonesia, Jl. Adi Sucipto Kelurahan Sidomulyo Timur, Kecamatan Marpoyan Damai, RT 001, RW 002, Kota Pekanbaru, Provinsi Riau., 2026)
This study aimed to examine the development, feasibility, and responses of students and teachers toward a comic-based learning media grounded in local wisdom for the topic of ecosystem harmony. The research was a development study that followed the ADDIE instructional model, consisting of five stages: analysis, design, development, implementation, and evaluation. However, this study was conducted only up to the development stage. The subjects involved were teachers, students, and validators, with data collected through interviews and student responses. The study concluded that the comic media based on Riau’s local wisdom was developed using the ADDIE model up to the development stage, involving needs analysis, story and illustration design, and validation by material, language, and media experts. The validation results indicated that the media was highly feasible, showing significant score improvements and positive responses from teachers (100%) and students (93.33%). The media was found to be engaging, effective in helping conceptual understanding, and relevant for use in IPAS learning. It is recommended that schools provide adequate digital facilities, teachers utilize this media in instruction, and future researchers develop an interactive version while investigating its effectiveness in improving student learning outcomes.